Quercetin attenuates pentylenetetrazol-induced seizures in chicks through antioxidant and anti-inflammatory pathways - Suleiman, Suleiman Dawood; Hasan, Jian Salam; Jarjees, Karwan Idrees; Haji, Aziza Raof (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study examines the neuroprotective and anticonvulsant effects of quercetin on pentylenetetrazol (PTZ)-induced convulsive seizures in chicks. Materials and Methods: Sixty Ross broiler chicks were randomly assigned to six groups: a negative control, a positive control treated with PTZ at 80 mg/kg, a diazepam-treated group (5 mg/kg), and three quercetin-treated groups receiving 50, 100, and 200 mg/kg orally for six consecutive days, respectively. Two hours after the final dose, PTZ was administered to groups 3-6 to induce seizures. The onset of convulsions and mortality rates were recorded over a period of 3 h. Brain tissue was collected to determine biochemical parameters, malondialdehyde (MDA), total antioxidant capacity (TAO-C), interleukin-1β (IL-1β), and tumor necrosis factor-α (TNF-α). Results: The delay in the onset of convulsions and survival improvement were found in quercetin pretreatment, in a dose-dependent manner. The highly significant survival was found at 200 mg/ kg (p < 0.001), and moderately at 50 and 100 mg/kg (p < 0.05). MDA (p < 0.05) and TNF-α (p < 0.01) levels were significantly decreased at all doses. TAO-C levels were significantly elevated, while IL-1β levels declined at 200 mg/kg (p < 0.05). Conclusion: Quercetin pretreatment at 200 mg/kg showed antioxidant and anti-inflammatory potential against PTZ-induced convulsive seizure as a preventive therapy for epilepsy management. J. Adv. Vet. Anim. Res., 12(3): 1037–1044, September 2025 http://doi.org/10.5455/javar.2025.l963